(untitled) (Research, Society and Development, 2021)
Every day countless people in Brazil and in the world are affected with tissue injuries caused by several factors that can generate significant skin losses. The body itself after a tissue injury begins the repair process, but when performed without pharmaceutical intervention, the process takes time and often this healing is not efficient and leaves sequelae. Aiming to circumvent this problem, a promising alternative for this purpose has been the use of pequi, a fruit typical of the Brazilian cerrado, rich in unsaturated fatty acids that has been used in folk medicine for its anti-inflammatory and healing effects in the treatment of various diseases. as well as in the rehabilitation of tissue injuries and, for this reason, they are targets of more detailed research in this work. This article is an integrative review on the potential of pequi in the treatment of wounds, having the privilege of uniting two scientific areas, which is the great Brazilian biodiversity and health under an interdisciplinary approach. For data collection, a bibliographic survey was carried out from 2014 to 2021 and from 2009 to 2021 for review and research journals, respectively. The searches were carried out, using the electronic databases of the VHL and indexed as LILACS, SCIELO, PubMed, Google academic and Science direct. Based on this bibliographic survey, it is possible to prove the spectrum of biological action of pequi when used in the treatment of wounds, presenting positive results in tissue repair and healing, confirmed through macroscopic, histological and clinical exams.